Synthesis and Characterization of Manganese(II), Cobalt(II), Nickel(II), Copper(II), Zinc(II) and Cadmium(II) Complexes of a Polydentate Ligand - Krishnan, G.; Babu, N. (Asian Journal of Chemistry, 2016)
A few complexes of Mn(II), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) with a polydentate ligand, N,N'-diethyleneamine-bis(3-carboxy propenamide) (DBCPH2) have been synthesized and characterized by elemental analysis, conductance, thermal, magnetic, IR, electronic spectra and X-ray diffraction methods.